STRATEGIC HUMAN CAPITAL PLANNING IN THE ASIAN DIGITAL ECONOMY: ALIGNING WORKFORCE DEVELOPMENT WITH BUSINESS OBJECTIVES - Loso Judijanto; Tengku Ine Hendriana; Caroline; A Fadel Muhammad; Syaepudin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research delved into Strategic Human Capital Planning (SHCP) in the Asian Digital Economy, examining the alignment of workforce development with business objectives. A comprehensive analysis encompassed the dynamic landscape of the Asian digital sector. Skill mapping was conducted to understand workforce capabilities and identify gaps and future skill requirements. Continuous learning initiatives were embraced, promoting a culture of adaptability and innovation. Leadership development programs were instituted, emphasizing both technical and soft skills. Tailored talent acquisition strategies sought candidates with diverse skill sets, aligning with the region's cultural nuances. Technology, including data analytics, facilitated data-driven insights for informed decision- making. Inclusivity and diversity were promoted, recognizing their value in fostering innovation. Challenges were addressed through proactive change management, targeted skill development, cultural sensitivity training, and clear communication channels. Incentives for adaptability and collaborative decision- making further facilitated successful implementation. The study concluded with practical recommendations for businesses navigating the complexities of the Asian Digital Economy, urging a strategic focus on human capital planning.